solve for x&y a(x+y)+b(x-y)=a2+b2+ab a(x-y)+b(x+y)=a2+b2-ab where 2 is used for squared

Asked by  | 22nd Apr, 2012, 09:06: AM

Expert Answer:

 a(x+y)+b(x-y)=a2+b2+ab
a(x-y)+b(x+y)=a2+b2-ab
 
Add the above 2 equaitons we get,
2ax+2bx=2(a2+b2)
 
x(a+b)=a2+b2
x= a2+b2/(a+b)
 
Now subtract the second equation from first equation to get
2(a-b)y=2ab
y=ab/(a-b)

Answered by  | 30th Apr, 2012, 02:04: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.